Thyroid cytology smear slides: An untapped resource for ThyroSeq testing. Issue 1 (22nd July 2020) - Nikiforova, Marina N.; Lepe, Marcos; Tolino, Lindsey A.; Miller, Megan E.; Ohori, N. Paul; Wald, Abigail I.; Landau, Michael S.; Kaya, Cihan; Malapelle, Umberto; Bellevicine, Claudio; Troncone, Giancarlo; Nikiforov, Yuri E.; et al.
Abstract : Background: Molecular testing of thyroid nodules with indeterminate fine‐needle aspiration (FNA) cytology is commonly used to guide patient management and is typically performed on freshly collected FNA samples. In this study, the authors evaluated the performance of the ThyroSeq test in cytology smear slides. Methods: Air‐dried Diff‐Quik (DQ)‐stained and alcohol‐fixed Papanicolaou (Pap)‐stained smears were used to determine required cellularity and sensitivity of mutation detection and to compare ThyroSeq v3 Genomic Classifier (GC) results obtained in cytology smears and fresh FNA samples from the same nodules. Results: ThyroSeq testing of 31 cytology smears revealed that 25 smears (81%) were adequate for ThyroSeq analysis, including 14 Pap‐stained smears (100%) and 11 DQ‐stained smears (65%), whereas 6 DQ‐stained smears (35%) failed RNA sequencing. The overall accuracy for detecting molecular alterations was 98%, with 100% concordance for mutations and gene expression alterations, 96% concordance for fusions, and 94% concordance for copy number alterations. Cytology smears were adequate for ThyroSeq analysis when at least 200 to 300 cells were present in 1 to 3 slides. ThyroSeq detected all studied mutations down to 5% allele frequency and BRAF mutations down to 1% allele frequency. Testing of smears yielded a positive ThyroSeq GC result in all nodules originally classified as positive. Conclusions: Thyroid FNA cytology smear slides with adequate cellularity can be successfully used for ThyroSeq GC testing in approximately 80% of cases, with an even higher success rate in Pap‐stained smears. Compared with FNA samples collected into preservative solution, 94% to 100% of different genetic alterations could be accurately detected in smears, validating cytology smears as an alternative for ThyroSeq testing in patients with indeterminate thyroid cytology. Abstract : Molecular testing of thyroid nodules is commonly used to inform the clinical management of patients who have indeterminate fine‐needle aspiration cytology results, and the ThyroSeq v3 Genomic Classifier (GC) test has been validated for clinical use on fine‐needle aspiration samples collected into preservative solution. The performance of the ThyroSeq v3 GC is evaluated in cytology smear slides, and its analytical validity and clinical utility in cytology smears are defined.